Analgesic efficacy of a laparoscopic-guided transversus abdominis plane block versus no transversus abdominis plane block in bariatric gastric bypass surgery a retrospective analysis among 332 individuals - Gianluca De Santo; Oliver Stumpf; Peter Look; Marc Abdelmalek; Rolf Lefering; René Mantke; Christoph Paasch (BMC Surgery)
Abstract Background To reduce opioid consumption and improve early mobility, the administration of a transversus abdominis plane block (TAP) was introduced in abdominal surgery decades ago. But the usefulness of this nerve block prior to laparoscopic Roux-Y gastric bypass (LRYGB) in patients with obesity is still under debate. Hence, the study at hand was conducted. Methods In 2023 a retrospective single-centre analysis among patients who did or did not receive a laparoscopic (L) TAP block prior to LRYGB was performed. The primary objective was the early postoperative pain level (1 h) using the visual analog scale (VAS) after LRYGB. Main secondary objectives were the determination of the pain level from 1 to 80 h after surgery and the cumulative postoperative painkiller use. Results A total of 111 individuals received and 202 did not receive a L-TAP block prior to LRYGB. The groups were homogeneous with respect to age, gender distribution and Body Mass Index. No L-TAP related complications occurred. After multivariate analysis the administration of the nerve block had no effect on relevant pain (VAS ≥ 6) from one to 80 h after LRYGB. One hour after surgery, the individuals who received the L-TAP suffered, with significance, from less pain (VAS score 2.77 vs. 3.84: p < 0.001) in comparison to those who did not receive the nerve block. No difference was revealed in terms of cumulative postoperative opioid painkiller use. Conclusion The L-TAP block is a safe procedure and sufficiently reduces post-operative pain one hour after gastric bypass surgery, but does not bring any benefits in the further course. Graphical Abstract